POLA-POLA SINGKATAN DAN AKRONIM PADA SURAT KABAR DAN IMPLIKASINYA SEBAGAI MATERI AJAR - Tri Wulandari; Mulyanto Widodo; Edi Suyanto (FKIP Universitas Lampung, 2013)
The problem under study is about how the patterns of abbreviations and acronyms that exist in the Kompas Daily Newspaper edition in January 2013 and their implications for teaching materials on junior high school. This study aimed to describe the patterns of abbreviations and acronyms in the Kompas Daily Newspaper edition in January 2013. The method used is descriptive qualitative method. After doing research, the dominant pattern of abbreviations found in the Kompas Daily Newspapers The first pattern is the perpetuation of the first letter of each component. While the acronym patterns are often found in the Kompas Daily Newspapers The fourth pattern is the perpetuation of the first letter of each component. Learning about the implications of abbreviations and acronyms contained in the Standar Kompetensi (SK) and the Kompetensi Dasar (KD) of the syllabus writing skills especially in dealing with spelling accuracy. Abbreviations and acronyms can be used as learning materials and assessment indicators, while the daily newspaper can be used as a medium of learning.Keywords: abbreviations, acronyms, newspaper